SISTEM TEMU KEMBALI INFORMASI PERUNDANG-UNDANGAN DENGAN MENGGUNAKAN BASIS DATA XML (Information Technology and Telematics, 2014)
Abstract -Law is a legal document that contains a binding legal norms in general and established or designated by the State agency or official author ities through established procedures. Currently the document is documented in text file format. XML format into a format suitable as a document Standard laws of the State because XML is a standard document that can separate the writing of the structure and content of the document. -Information retrieval legislation using xml database with a natural language interface. Natural language interface is used to facilitate the acquisition of information legislation  documents that fit the needs of information retrieval. To use the web interface implemented using the programming language Java Server Pages. Users of this system have the ease in operating the system. -How to get using input means asentence in Indonesian, with predetermined grammar. In this application also given examples of how to provide input sentence. The out put of this application in the form ofa table to the user, if the input sentence given is correct and the data in accordance with the request. Data shownis the result of Xquery based on those data retrieval. If the pattern is not in accordance with the rules of the question then posed by these applications is a warning error. Keywords: Law, Information Retrieval, XML, XQuery